Cassava Wastewater Treatment in Fixed-Bed Reactors: Organic Matter Removal and Biogas Production - Watthier, Elisangela; Andreani, Cristiane L.; Torres, Douglas G. B.; Kuczman, Osvaldo; Tavares, Maria H. F.; Lopes, Deize D.; Gomes, Simone D. (Frontiers in Sustainable Food Systems, 2019)
The process of cassava starch extraction is associated with the generation of a large volume of liquid wastes from root washing and starch extraction (5 to 7 L.kg-1root). In this context, the objective of this study was to evaluate the treatment of cassava starch wastewater in a horizontal anaerobic fixed bed reactor to the removal of organic matter and generation of biogas. For this purpose, two fixed bed reactors filled with two different types of support materials were used: bamboo rings and flexible PVC rings. The reactors were constructed in polyvinyl chloride (PVC) with 90 cm length and 15 cm diameter. The working volume of R1 (bamboo as support material) and R2 (PVC as support material) were 6.0 and 8.0 L, respectively. In the operation of the reactors, 13 assays (A1 to A13) were carried out with an increase in the organic loading rate (OLR: 1.7 to 15.0 g COD.L-1.d-1) and a decrease in the hydraulic retention time (HRT: 4.0 to 0.8 days). Biogas production followed a similar pattern in both reactors. The highest biogas productions of 1.5 L.L-1.d-1 (R1) and 1.1 L.L-1.d-1 (R2) were verified in the assay 6 in which were applied highest affluent concentration (15,122 mg.L-1), intermediates organic loading rate (5.6 g.L-1.d-1) and hydraulic retention time (2.7 d). The removal of COD increased with the increase of OLR resulting in COD removal values of up to 99%. Total solids removal efficiencies of 79 and 87% were achieved in R1 and R2, respectively. In both reactors, the contact surface of bamboo (132 m2.m-3) and PVC (191 m2.m-3) supported biomass attachment even in highest OLR (15 g.L-1.d-1) and low HRT (0.8 d). The both support material provided conditions to the reactors withstand the variations and reestablish the equilibrium after possible hydraulic and load shocks, constituting a robust system for the treatment of cassava starch wastewater. In these conditions the COD and solids removal remained satisfactory. After a 450-day reactor running, no changes were observed in the composition and structure of the support material, an indication that bamboo and PVC are possible cheap and efficient alternatives for biomass immobilization.